Watermass structure In the Western Indian Ocean : Part I-Watermasses and their thermohaline indices (MAUSAM, 1986)
The concept of "Indian Ocean Common Watermass" is introduced and its  characteristics are defined. The temperature-salinity structures which would result when one, two or  more watermasses of different temperature and salinity characteristics penetrate into the layer of the Indian Ocean Common Water are discussed. The thermohaline indices of different watermasses in the western Indian Ocean are derived and tabulated.